2017
DOI: 10.1093/mnras/stx2160
|View full text |Cite
|
Sign up to set email alerts
|

Determining the torus covering factors for a sample of type 1 AGN in the local Universe

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 80 publications
9
30
0
Order By: Relevance
“…This is consistent with the very weak covering factor of 0.06 for the putative torus, which is inferred from the ratio of the infrared to the bolometric luminosity of the source (Ezhikode et al 2017). Moreover, the torus covering factor measured for Mrk 110 is one of the lowest reported in the Ezhikode et al (2017) sample; this is also in agreement with the lack of Compton hump. The equivalent widths of the moderately broad Fe Kα line are EW b = 61 +23 −27 eV and EW b = 43 +22 −27 eV for 2019 and 2020, respectively.…”
Section: Main X-ray Spectral Components Of the 2019 And 2020 Xmm-newton And Nustar Observationssupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with the very weak covering factor of 0.06 for the putative torus, which is inferred from the ratio of the infrared to the bolometric luminosity of the source (Ezhikode et al 2017). Moreover, the torus covering factor measured for Mrk 110 is one of the lowest reported in the Ezhikode et al (2017) sample; this is also in agreement with the lack of Compton hump. The equivalent widths of the moderately broad Fe Kα line are EW b = 61 +23 −27 eV and EW b = 43 +22 −27 eV for 2019 and 2020, respectively.…”
Section: Main X-ray Spectral Components Of the 2019 And 2020 Xmm-newton And Nustar Observationssupporting
confidence: 88%
“…For the narrow core of the Fe Kα line, we measure a EW n 20 eV, which is in the lower range of the values found for type-1 AGN (∼30−200 eV; Liu & Wang 2010;Shu et al 2010;Fukazawa et al 2011;Ricci et al 2014). This is consistent with the very weak covering factor of 0.06 for the putative torus, which is inferred from the ratio of the infrared to the bolometric luminosity of the source (Ezhikode et al 2017). Moreover, the torus covering factor measured for Mrk 110 is one of the lowest reported in the Ezhikode et al (2017) sample; this is also in agreement with the lack of Compton hump.…”
Section: Main X-ray Spectral Components Of the 2019 And 2020 Xmm-newton And Nustar Observationssupporting
confidence: 82%
“…Other physical drivers may contribuite to make the physical properties and the geometry of the system -and therefore the SED -different. In the case of the torus, both primary source properties -such as the accretion rate (Ricci et al 2017;Ezhikode et al 2017) or the luminosity (Maiolino et al 2007;Treister et al 2008;Lusso et al 2013), and composition of the torus clouds (Audibert et al 2017;Ramos Almeida et al 2011;Alonso-Herrero et al 2011) can change the shape of the IR emission. We do note again, however, that, as for this study has been designed, the effects produced by drivers other than orientation are "blended" within the EW[O iii] bins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the infrared band indicate that the torus covering factor may be a function of luminosity (e.g., Maiolino et al 2007, Treister et al 2008, Assef et al 2013, and may correlate with other measurable properties (e.g., presence of broad lines in optical spectra; Mateos et al 2016). It has been suggested that the covering factor depends on the Eddington ratio (e.g., Ezhikode et al 2017, Buchner & Bauer 2017, Ricci et al 2017b, and that its dependence on luminosity or the Eddington ratio changes with redshift (e.g., Aird et al 2015, Buchner et al 2015. AGN population studies in the X-ray band suggest that the fraction of obscured AGN drops as a function of luminosity (e.g., Sazonov & Revnivtsev 2004, Hasinger 2008, Burlon et al 2011, Vasudevan et al 2013.…”
Section: Introductionmentioning
confidence: 99%